The Role of Green Architecture in Smart Cities (Journal of Architectural Design, 2022)
Since the last few years, the concept of "smart cities" has become a widespread topic in a variety of fields. The practice of sustainable development is to thank for this rise in popularity. The philosophy, physics, and aesthetics of ecologically friendly building design and construction are collectively referred to as "green architecture" or "green building." The goal of green design is to reduce the amount of resources used in the construction, usage, and operation of a building, as well as the pollution, waste, and emissions that result from these activities. Design and construction of buildings generatorbaes waste that is harmful to human health and the environment. In order to minimize these resource-efficient structures and negative effects and build environmentally sound, it is necessary to introduce, define, understand, and practice green architecture. There is a word for environmentally friendly architecture. There are many benefits to adopting the principles of "Green Architecture" and "Green Building" in order to better utilize the natural environment and renewable energy sources, and then to creating standards for energy efficiency in buildings .